2013
DOI: 10.1080/10242694.2013.763438
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Problems in Military Expenditure Data Using Digital Analysis

Abstract: The UN asks governments to report key figures of their annual military budgets with the aim of creating trust among member states. This goal can only be achieved if the data reported is accurate. However, although there are many reasons for governments to falsify data, the UN does not check for manipulation. In this paper, we apply Benford's law to the military expenditure data of 27 states taken from the UN register. Our analysis of the first digits shows that the states with the greatest deviations from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Articles investigating EM at a macro-level perspective principally used the stock-flow adjustments approach, defined as the difference between the budget deficit and the change in public debt (von Hagen and Wolff, 2006;Reischmann, 2016;Maltritz and W€ uste, 2020) or used Benford's law (e.g. Rauch et al, 2011Rauch et al, , 2014. Six articles (about 8%) used other research methods, such as structured equation modeling (e.g.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Articles investigating EM at a macro-level perspective principally used the stock-flow adjustments approach, defined as the difference between the budget deficit and the change in public debt (von Hagen and Wolff, 2006;Reischmann, 2016;Maltritz and W€ uste, 2020) or used Benford's law (e.g. Rauch et al, 2011Rauch et al, , 2014. Six articles (about 8%) used other research methods, such as structured equation modeling (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…about 38% in both cases). Nine articles investigated America, while three studies concentrated on a sample of countries from several continents (Rauch et al , 2014; Reischmann, 2016; Kartiko et al , 2018).…”
Section: Research On Earnings Management In the Public Sector: Insigh...mentioning
confidence: 99%
“…& Stoltz 2013, Nye & Moul 2007), and military expenditures (Rauch et al 2014). Interestingly, of the 27 countries reporting military data to the United Nations, the United States and United Kingdom had the lowest conformance with Benford's law, indicating the lowest data quality.…”
Section: Percentage Of Observations Per Binmentioning
confidence: 99%
“…Google Scholar (http://scholar.google.com) reports that the RGBE paper has 57 citations. Rauch, Göttsche, and Langenegger (2014) analyzed military expenditures reported to the United Nations Office for Disarmament Affairs. They concluded that the United States and the United Kingdom have the lowest quality military data because they had the worst conformity to Benford.…”
Section: Analysis Of Data Subsetsmentioning
confidence: 99%